2003
DOI: 10.1002/ajmg.b.20122
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for an association between WNT2 and RELN polymorphisms and autism

Abstract: Autism is a pervasive neurodevelopmental disorder characterized by deficits in language development and social interaction, as well as stereotypical, repetitive behaviors. The etiology of autism is largely unknown. Family and twin studies have provided compelling evidence for a strong genetic component in most idiopathic cases. Several recent candidate gene studies have suggested that alleles of WNT2 and the reelin gene (RELN), two genes involved in distinct aspects of neurodevelopment, confer greater suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 39 publications
(38 reference statements)
3
56
1
1
Order By: Relevance
“…region before the start codon, have reached conflicting results. [43][44][45][46][47][48][49] This may reflect only the common pattern of nonreplication of early claims from small studies 50 or a modest effect may still be present. A large study should be conducted on this association.…”
Section: Discussionmentioning
confidence: 99%
“…region before the start codon, have reached conflicting results. [43][44][45][46][47][48][49] This may reflect only the common pattern of nonreplication of early claims from small studies 50 or a modest effect may still be present. A large study should be conducted on this association.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies did find an association, [176][177][178] five other studies of comparable size and power did not find an association of the 5 0 UTR trinucleotide or other variants with AD. [179][180][181][182][183] The first positive finding 176 reported an association with the relatively rare longer alleles ( > 10) of the 5 0 UTR trinucleotide polymorphism with AD. However, in another study, 178 the most common repeat 10 was over-represented in AD.…”
Section: Chromosomementioning
confidence: 99%
“…189 The first study 17 reported a nominal association of a 3 0 UTR 783C > T SNP detected by mutation analysis in two affected siblings with AD. Subsequent studies 182,190 could not replicate this finding. Despite an established role of WNT2 in the development of the vertebrate central nervous system, its function in human brain development has not yet been proven.…”
mentioning
confidence: 91%
“…[150][151][152] Fatemi et al 153,154 have shown that levels of RELN mRNA and Reelin protein are significantly deficient in the brain of autistic subjects. RELN plays multiple roles in brain, including cell guidance during embryonic development, and mediation of neurotransmission and synaptic plasticity in adulthood.…”
Section: Autism Candidate Genes and Synaptic Functionmentioning
confidence: 99%